Spectroscopic investigation of fluorinated monophosphate tungsten bronzes - Stus, N.V.; Lisnyak, V.V.; Slobodyanyk, M.S. (Functional Materials, 2004)
Novel materials, silver-containing type of monophosphate tungsten bronzes with hexagonal channels (МВТВЛ), Ag4(WO3)g(PO2)4, and fluorinated analogues (FMBTB^), Ag4(WO3_xFx)8(PO2)4, where 0 < x < 0.05, containing silver atoms in different valence states have been synthezised and studied using X-ray photoelectron spectroscopy, pho -toemission electron microscopy, and resistivity measurements. The resistivity anomalies observed for FMBTBk may testify to the electron instability state realization at temperatures about 150 to 250 K.